PENGARUH PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII SMP - Nafi’i, Fiqi Fathnin; Yuliastuti, Rita (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research is motivated by the fact that there is still a lack of students' understanding of the material presented, resulting in students having difficulty solving mathematical problems. This study aims to examine whether there is a significant effect of the application of a realistic mathematical approach to the mathematical problem solving abilities of Grade VIII students of junior high school. This research is a quantitative study using pre-test and post-test control group experimental designs. The study population was all students of class VIII SMP Negeri 4 Tuban with a total of 256 students, with a sample of 32 students in class VIII C as the control class and class VIII D as an experimental class of 32 students and were selected using cluster random sampling technique. In this study the experimental class will be subjected to a realistic mathematical approach while the control class will be subjected to conventional learning. Data collection techniques used are tests and observations. The observation method is used to find out whether the application of a realistic mathematical approach is working or not in learning, both seen in the activities of teachers and students. Meanwhile, the test method is used to obtain data about mathematical problem solving abilities on the subject of Statistics. This test technique was carried out after the treatment was given to the experimental class and control class with the aim of obtaining final data. The data analysis technique used is the t-test. Through the t-test it can be seen that the average post-test score of the control class students was 64.06 and the average post-test score of the experimental class students was 74.47. The results of the study show that there is a significant effect of applying a realistic mathematical approach to students' mathematical problem solving abilities.